A Multi-Theoretical Perspective on Blockchain Adoption in Tea Supply Chain Optimization: Analyzing Drivers and Barriers through Theories - Hillan, Ronoh (Universitas Komputer Indonesia, 2027)
Blockchain technology has emerged as a transformative innovation in supply chain management (SCM), improving transparency, traceability, and efficiency. This study adopts a multi-theoretical perspective by integrating six organizational theories—Principal-Agent Theory, Transaction Cost Analysis, Resource-Based View, Network Theory, Institutional Theory, and Information Theory—to examine the drivers and implications of blockchain adoption in SCM. Each perspective explains how blockchain mitigates agency conflicts, lowers transaction costs, functions as a strategic resource, strengthens collaborative networks, responds to institutional pressures, and enhances information processing. Using the tea supply chain as an illustrative context, this study proposes a conceptual framework linking blockchain features—such as immutability, smart contracts, and decentralization—with SCM goals including trust, accountability, cost efficiency, and competitive advantage. The synthesis provides insights for developing scalable and context-relevant blockchain applications across supply chain systems.